Views on the momentous past of Alleppey : between alappuzha then and Alappuzha now - Schenk, Hans (New Delhi : Manohar, 2025)
This book explores the rich and significant history of Alleppey, beginning with the casual British mispronunciation of a small village in Travancore: Alappuzha. In 1762, this modest hamlet was transformed into a planned seaport by the Rajah of Travancore to facilitate the lucrative spice trade. The narrative of Alleppey concludes with the reinstatement of its original name in 2012. At its core, the book seeks to understand how and why Alleppey evolved$1 (Bboth positively and negatively$1 (Binto a port and industrial hub in South India. It traces the city$1 (Bs developmental phases from its inception in 1762, examining the political, socio-economic, and spatial dynamics that shaped its periods of prosperity and decline. As a result, the book presents a multi-dimensional study. It investigates the roles played by the semi-autonomous Travancore state, British colonial authority, and both local and foreign merchants and industrialists involved first in the spice trade and later in coir production. Equal importance is given to Alleppey$1 (Bs unique geography, dominated by waterways, as well as to its transport infrastructure and technological environment. The book deals as well with local labour conditions and the emergence of trade unions and revolutionary political movements during the twentieth century. Finally, the book considers how Alleppey$1 (Bs inhabitants perceived the dramatic economic decline during the latter half of the twentieth century, and how former economic powerholders reacted to the fading away of their erstwhile might. About the Author Hans Schenk was affiliated with the University of Amsterdam, where he engaged in teaching, research, and development work, particularly centered on urban Asia. He wrote extensively on urban matters, drawing from his work in various Indian and other Asian towns and cities, both large and small.s
Keywords: Alleppey-History; Alleppey-Society and Culture; Travancore-History; Alappuzha-History